100 new scientific discoveries fascinating, unbelievable and mind-expanding stories - Kluger, Jeffrey; Time Inc. Home Entertainment (New York, N.Y. TIME Books, 2011)
A collection of stories about groundbreaking scientific discoveries covers such topics as animal behaviors, the characteristics of distant galaxies, and the incredible capacity of the human mind, in a volume that also provides a chronology of debunked scientific theories.
Introduction -- The cosmos -- The mind -- Technology -- Archaeology -- Genetics -- Physics -- Medicine -- The Earth -- Zoology -- Chemistry.
Keywords: Discoveries in science; Discoveries in science